ANALISIS ALIH KODE DAN CAMPUR KODE DALAM NOVEL BUMI CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Maulina, Maulina; Patriantoro, Patriantoro; Lasmono, Djon (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â This study focused on Code Transfer and Code Mixing in the Bumi Cinta novel by Habiburrahman El Shirazy. Code switching is the transfer of language from Indonesian to another language, while mixing code is mixing Indonesian with other languages.The problem of this research is how is the type of code switching, how does the type of code intervene, and how does the code mix form in the novel Bumi Cinta by Habiburrahman El Shiray. The purpose of this study was to describe the type of code switching, describe the type of code mixing, and describe the mixed code form in the novel Bumi Cinta by Habiburrahman El Shirazy. The technique used is documentary study techniques. Data collection tools are humans as keys and note cards.Based on the results of data analysis of code switching and code mixing, this study found 28 types of code switching outside, namely code switching from Indonesian to Russian, from Indonesian to Arabic, and from Indonesian to English. There are 3 types of mixed code in, from Indonesian to Javanese. There are 40 types of mixed code out, from Indonesian to Russian, from Indonesian to Arabic, and from Indonesian to English.Â Keywords: Code switching, Code mixing, Novel